Analısıs kualıtatıf senyawa rhodamın B pada saus jajanan “tusuk-tusuk” dı taman Berkampung kota Tarakan menggunakan metode rapid test kit - Faizal Mustamin; Irma Novrianti; Muhammad Aris; Asma Asma (Journal Borneo, 2022)
Food is a basic need for living things. Some foods are available in the form of snacks and usually contain additional ingredients such as coloring. Often manufacturers misuse the use of dyes for textiles such as rhodamine B and leather used to color food ingredients. This study aims to determine the content of rhodamine B in the "tusuk -tusuk" snack sauce circulating in the village garden. The sauce is obtained from each seller of "skewers" selling in the village garden. This study used 25 samples, then 25 grams were taken from each sample and dissolved in hot water, and then the samples were tested using the rapid test kit method. Based on the results of the study, it was found that the negative sauce samples contained rhodamine B. Based on these results, it can be concluded that the " tusuk -tusuk " snack sauce in the village gardens of Tarakan city does not contain rhodamine B.